Scientometric analysis of scientific production on the genus Campomanesia Ruiz & Pav. (Myrtaceae) and most studied species - research trends involving native Brazilian plants (Research, Society and Development, 2022)
Brazil has rich biodiversity, harboring native plants with potential for medicinal use, including species of the Campomanesia genus. Although public policies to encourage phytotherapy advocate the best use of plant biodiversity, most species listed in official forms and monographs are exotic species. Thus, the aim of this study is to identify research trends involving the Campomanesia and main species, using scientometric tools, so that, by viewing and knowing the scientific production on the genus and species of pharmacological interest, possibilities for research with native species so that they can be integrated into Brazilian’s unified health system (SUS). The research resulted in 302 publications up to September 2021. Bibliometric analyzes on genus were then carried out with data from the WoS platform and social network analysis through of scientometric mapping, using the Vosviewer (VOS) application. Species of the genus with more than 10 publications indexed in WoS were also analyzed. Brazil leads research on the genus and C. xanthocarpa (120/302); C. adamantium (70/302); C. pubescens (33/120); C.phaea (25/302); C. lineatifolia (21/302) and C. guazumifolia (10/302) were the species with the highest publication volume. It is the first work that analyzes the scientific production on these genus of Myrtaceae family and the aforementioned species, which revealed itself a promising field of research, yet little explored, which might encourage new studies aimed at better use of Brazilian biodiversity and the safe and effective use of native plants that may bring benefits to people's health and well-being.